(untitled) (Élisée - Revista de Geografia da UEG, 2021)
Studies dedicated to the urban climate and the atmosphere of cities have long revealed the concern with urban heating in relation to the surrounding rural areas, in what has become generally known as urban heat islands. In this article, atmospheric heat islands were investigated at the level of the urban canopy (OKE, 1987), considering the theoretical and methodological scope of the Urban Climate System (MONTEIRO, 1976) in a study applied to Santo Anastácio, a small city located in the western region of the state of São Paulo, Brazil. To achieve the purposes of the study, air temperature records were made at 9:00 PM between April and December 2017, in points representative of the urban and rural areas, through which heat intensities were obtained taking the rural area as a reference. The results confirm the configuration of heat islands of weak, moderate and strong magnitude, as well as cold islands alternating in the presence of different types of weather. The frequency of the magnitudes varied according to the types of weather and the geo-environmental and urban characteristics of the representative points. The results demonstrate the importance of incorporating knowledge in climatology for urban planning and organization that is resilient to thermal discomfort, particularly in the continental tropical environment.